Aggregation-induced circularly polarized phosphorescence of Pt(ii) complexes with an axially chiral BINOL ligand. Issue 27 (14th March 2023) - Tauchi, Daiki; Koida, Taiki; Nojima, Yuki; Hasegawa, Masahi; Mazaki, Yasuhiro; Inagaki, Akiko; Sugiura, Ken-ichi; Nagaya, Yuki; Tsubaki, Kazunori; Shiga, Takuya; Nagata, Yuuya; Nishikawa, Hiroyuki
Abstract : A pair of chiral Pt(ii ) complexes exhibiting aggregation-induced phosphorescence and circularly polarized luminescence have been synthesized and characterized. Abstract : A pair of chiral Pt(ii ) complexes coordinated by simple BINOL and bipyridine ligands displaying aggregation-induced phosphorescence and circularly polarized luminescence were characterized by X-ray crystallography and absorption and emission spectroscopies. The emission of the powder sample was reddish whereas the thin film dispersed in PMMA ( f Pf = 1 wt%) exhibited a white emission.